Analgesic efficacy of continuous serratus anterior plane block versus intercostal nerve block and their combination in VATS lobectomy: results from a prospective randomized trial - Lim, Hyun Ah; Rim, Gongmin; Hyun, Kwanyong; Chang, Yong Jin; Cho, Deog Gon (Frontiers in Surgery, 2025)
BackgroundEffective postoperative pain management following video-assisted thoracoscopic surgery (VATS) lobectomy is essential to optimize recovery and minimize opioid consumption. This study aimed to compare the analgesic efficacy of ultrasound-guided continuous serratus anterior plane block (SAPB), intercostal nerve block (INB), and their combination (SAPB + INB) in patients undergoing VATS lobectomy.MethodsIn this single-center, single-blinded, randomized controlled trial, 90 patients undergoing VATS lobectomy for confirmed or suspected lung cancer were randomly assigned to one of three groups: INB (n = 30), continu.ous SAPB (n = 30), or SAPB + INB (n = 30). The primary outcome was postoperative pain assessed using the visual analog scale (VAS) at 24 h. Secondary outcomes included VAS scores at 1, 3, 6, 12, 48, and 72 h postoperatively, cumulative opioid consumption, length of hospital stay, and postoperative complications.ResultsNo significant differences in VAS scores were observed among the three groups at 24 h postoperatively. All groups maintained acceptable pain levels (VAS < 4) throughout the study. However, opioid consumption was significantly lower in both the SAPB and SAPB + INB groups compared to the INB group at all time points (p < 0.01).ConclusionsContinuous SAPB, INB, and SAPB + INB were all effective for postoperative pain management after VATS lobectomy. However, INB alone was associated with significantly higher opioid use. Given its technical simplicity, prolonged analgesic effect, and opioid-sparing properties, continuous SAPB represents a valuable component of multimodal analgesia in enhanced recovery protocols. Clinical Trial RegistrationIdentifier KCT0009683.